Effect of Iron, KNO3, GA3 and Humic acid on Growth and Leaf Nutrients of Almond (Prunus amygdalus L.) Transplants 1-Vegetative Growth - Mayi, Azad A. (Science Journal of University of Zakho, 2016)
This investigation was conducted during the growing season of 2011-2012, in the nursery of the Malta station/ Duhok. Kurdistan region, Iraq. On two year old Almond transplants, grown in polyethylene bags. The transplants were foliar sprayed two times; 20th April , 10th May 2011, with three levels of Iron (0, 40, 80 mg.l-1), three levels of GA3 (0, 250 and 500 mg.l-1), four levels of KNO3 (0, 50,100, and 200 mg.l-1) and three levels of Humic acid (0, 25 and 50 mg.l-1). The transplants were left under nursery conditions till 1 October, 2011. The experimental was arranged as Factorial including Randomized Complete Block Design (R.C.B.D) with five replicates with five transplants per unit. Foliar spray of Humic acid at 50mg.l-1 increased significantly stem diameter (0.57 cm, lateral shoot length (25.33 cm), lateral shoot number (20.67), leaves number (62.67), leaves fresh (6.30%) and dry weight (3.33%). GA3 at 250 mg.l-1significantly increased leaves area (12.56 cm2), shoot fresh weight (25.4%), and dry weight (15.22%) and root length (38cm). However, 40mgFe.l-1 increases significantly chlorophyll content (66.63%). While, KNO3 significantly affected on root fresh weight (13.16 %), and dry weight (7.62%).